Optimal Weights and Stress Banking Indexes - Stefano Puddu (University of Neuchâtel, Institute of Economic Research (IRENE), 2013)
The goal of this paper is to provide alternative approaches to generate indexes in order to assess banking distress. Specifically, we focus on two groups of indexes that are based on the signalling approach and on the zero in ated Poisson models. The results show that the indexes based on these approaches perform better than those constructed by using the variance-equal and the factor analysis methods. Specifically, they are better at capturing relevant events, signalling distress episodes and forecasting properties. The importance of this study is two-fold: first, we contribute extra information that can be useful for forecasting banking system soundness in the aim of preventing future financial crises; second we provide alternative methods for measuring banking distress.
Keywords: C16; C25; G21; G33; G34; 330; Stress-banking indexes; Signalling approach; Limited dependent variable methods